The Impact of Sowing Systems on the Grain Yield of Maize - Dominik Mikolčević; Anamarija Banaj; Đuro Banaj; Ranko Gantner; Željka Banaj (Poljoprivreda)
A research on two maize-sowing systems was conducted on the locations Radnovac (L1) and Kujnik (L2) during 2021 and 2022. A standard sowing (SR), implying a row spacing amounting to 70 cm, was carried out by a PSK4 (S1) pneumatic vacuumsowing machine. A sowing in the twin rows (TR), with a distance amounting to 22 cm, and a distance between the two adjacent rows amounting to 48 cm, was performed by a MaterMacc Twin Row 2, which is also a pneumatic vacuum-sowing machine (S2.). Three different maize hybrids were sown, and the sowing speed was 6 km h-1. The largest and the smallest difference in the number of plants was determined in 2021 on the location L1 and amounted to 2,899 and 1,183 plants ha-1. On the location L2, the number of plant differences was between 1,511 and 1,644 plants ha-1 in the TR sowing. In the research year 2021, no statistically significant differences in grain yield kg ha-1 between the sowing systems were recorded on the location L1. However, in 2022, it was statistically confirmed that sowing in the twin rows produced a higher grain yield on both locations, L1 and L2, respectively. The largest difference in yield was recorded on the L2 location in 2022.